CRACK INITIATION AND GROWTH IN BIMETALLIC GIRTH WELDS - A. Carlucci; BONORA, Nicola; GENTILE, Domenico; IANNITTI, Gianluca; RUGGIERO, Andrew (Volume 6A: Pipeline and Riser Technology, 2014)
Bimetallic girth welds are characteristics of clad pipe technology. When dealing with propagation issues, fracture mechanics concepts usually are no longer applicable as a result of the extensive and non-homogeneous plastic deformation along bi-material interface that occur at the crack tip even below design allowables. In this study, ductile crack initiation and propagation in bi-material girth welds was investigated using a Continuum Damage Mechanics (CDM) model proposed by Bonora [1]. For the base, weld and clad metal, ductile damage model parameters have been determined by means of inverse calibration technique using fracture data obtained on smooth and round notched tensile bar specimens. Firstly, the damage model was validated predicting ductile crack growth occurring in single end notch (SEN(T)) geometry sample comparing the applied load vs crack mouth opening displacement with experimental measurements. Successively, the model was used to investigate ductile crack initiation and propagation for under clad circumferential weld crack under remote tension